Molecular detection of eukaryotes in a single human stool sample from Senegal. - Ibrahim Hamad (Public Library of Science (PLoS), 2012)
Background Microbial eukaryotes represent an important component of the human gut microbiome, with different beneficial or harmful roles; some species are commensal or mutualistic, whereas others are opportunistic or parasitic. The diversity of eukaryotes inhabiting humans remains relatively unexplored because of either the low abundance of these organisms in human gut or because they have received limited attention from a whole-community perspective. Methodology/principal finding In this study, a single fecal sample from a healthy African male was studied using both culture-dependent methods and extended molecular methods targeting the 18S rRNA and ITS sequences. Our results revealed that very few fungi, including Candida spp., Galactomyces spp., and Trichosporon asahii, could be isolated using culture-based methods. In contrast, a relatively a high number of eukaryotic species could be identified in this fecal sample when culture-independent methods based on various primer sets were used. A total of 27 species from one sample were found among the 977 analyzed clones. The clone libraries were dominated by fungi (716 clones/977, 73.3%), corresponding to 16 different species. In addition, 187 sequences out of 977 (19.2%) corresponded to 9 different species of plants; 59 sequences (6%) belonged to other micro-eukaryotes in the gut, including Entamoeba hartmanni and Blastocystis sp; and only 15 clones/977 (1.5%) were related to human 18S rRNA sequences. Conclusion Our results revealed a complex eukaryotic community in the volunteer's gut, with fungi being the most abundant species in the stool sample. Larger investigations are needed to assess the generality of these results and to understand their roles in human health and disease.